2023
DOI: 10.1002/brb3.2965
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod ameliorates chronic experimental autoimmune neuritis by modulating inflammatory cytokines and Akt/mTOR/NF‐κB signaling

Abstract: Objective Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an immune‐mediated disease that targets the myelin sheaths of the peripheral nerves. Fingolimod is a sphingosine 1 phosphate (S1P) receptor antagonist with a high affinity for S1P receptors through the Akt–mTOR pathway, and prior research has suggested that it might be helpful in autoimmune illnesses. Methods Chronic experimental autoimmune neuritis (c‐EAN) was induced by immunizing Lewis rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Akt can activate the downstream NF-κB pathway, leading to phosphorylation of p65, thus promoting the expression of in ammatory factors. Alleviate the in ammatory reaction of sciatic nerve by regulating Akt/mTOR/NF-κB pathway [26,27] . QRT-PCR and Western Blot analysis showed that treatment with salidroside reduced the mRNA and protein expression of AKT, NF-KB, and TNF-α both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Akt can activate the downstream NF-κB pathway, leading to phosphorylation of p65, thus promoting the expression of in ammatory factors. Alleviate the in ammatory reaction of sciatic nerve by regulating Akt/mTOR/NF-κB pathway [26,27] . QRT-PCR and Western Blot analysis showed that treatment with salidroside reduced the mRNA and protein expression of AKT, NF-KB, and TNF-α both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%